2018
DOI: 10.3390/ijerph15040661
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Epidemiology of Viral Hepatitis in China (2003–2015): Implications for Prevention and Control Policies

Abstract: Viral hepatitis, as one of the most serious notifiable infectious diseases in China, takes heavy tolls from the infected and causes a severe economic burden to society, yet few studies have systematically explored the spatio-temporal epidemiology of viral hepatitis in China. This study aims to explore, visualize and compare the epidemiologic trends and spatial changing patterns of different types of viral hepatitis (A, B, C, E and unspecified, based on the classification of CDC) at the provincial level in Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 41 publications
1
39
1
Order By: Relevance
“…Thus, only one value is derived to determine if spatial association exists (that is if similarly valued tracts tend to be neighbors). The global Moran's I model uses a Moran's I value, a z-score, and a p-value to formally test the null hypothesis of spatial randomness in a dataset [52]. The global Moran's I statistic evaluates whether a clustered, dispersed, or random spatial pattern exists [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, only one value is derived to determine if spatial association exists (that is if similarly valued tracts tend to be neighbors). The global Moran's I model uses a Moran's I value, a z-score, and a p-value to formally test the null hypothesis of spatial randomness in a dataset [52]. The global Moran's I statistic evaluates whether a clustered, dispersed, or random spatial pattern exists [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that HEV is very endemic in eastern and south‐eastern Asian countries. In China, HEV prevalence is increasing from a high starting point (Zhu, Liu, Fu, Zhang, & Mao, ). Simultaneously, HEV prevalence has become greater in European countries as confirmed hepatitis E cases have increased over 10‐fold between 2005 and 2015 (Aspinall et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The null hypothesis is that the trends of geographical units in different windows are the same, while the alternative hypothesis is that the trends are different. On the basis of the hypotheses, the difference in the rates of change inside and outside the windows is evaluated by the Log Likelihood Ratio (LLR, Formula 3.2) [27], which is lower the more likely it is that the trend difference is due to chance.…”
Section: Space-time Scan Statisticsmentioning
confidence: 99%